Penerapan model pembelajaran problem-based learning dalam meningkatkan kemampuan pemahaman konsep matematika siswa - Rauf, Ila Ali; Samura, Asri Ode; Djawa, Yani (Journal of Didactic Mathematics, 2024)
This study investigated the effectiveness of problem-based learning (PBL) model in improving seventh-grade students’ conceptual understanding of mathematics at SMP Negeri 13, Ternate City, Indonesia. This study used a quantitative approach using a pre-experimental design, specifically a one-group pretest-posttest design. The sample consisted of 34 seventh-grade students at one of the public junior high schools in Ternate City. Data were collected using a written test, and analysis was conducted using inferential statistics, specifically the Paired Sample T-Test. The findings showed that the implementation of the PBL model significantly improved students’ ability to understand mathematical concepts, with the results showing a medium effect size. In addition, the effect size test classified the impact of PBL on students’ mathematical understanding in the high category.